A Structural Model of Cultural Tourism Supply Chain Collaboration on the R3A Route - Pairach Piboonrungroj; Benjenop Buranasiri; Wasittee Moonpim; Pimpika Chawalit; Korawan Sangkakorn (International Journal of Supply Chain Management, 2016)
This paper aims to evaluate the supply chain collaboration in the cultural tourism on the R3A route, which is starting from Kunming (China) to Luang Namtha (Lao PDR) and to Chiang Rai (Thailand). The Structural Equation Model (SEM) was used to evaluate the key factors that have affected to the collaboration between partners along the route. Data were collected from 200 cultural tourism enterprises via self-administrative questionnaires. The result was found that lack of data sharing is the barriers of collaboration on cultural tourism in R3A route between supply chain partners. Information, commitment, and communication technology are the key factors to promote collaboration sustainability.